Cornelius Castoriadis y el imaginario político - Arribas, Sonia (Foro Interno, 2008)
This article reconstructs from a linguistic perspective Cornelius Castoriadis’ theory of the political imaginary of society. After a detailed analysis of its main characteristics, this article suggests that the concept of the imaginary is very similar to Nietzsche’s notion of the Dionysian. Following Nietzsche in his self-criticism and later abandonment of the Dionysus and Apollo duality, and thanks to his genealogical and linguistic model of the political and social spheres, this article concludes with an alternative reading of the imaginary, as a critical approach.
Keywords: Castoriadis; Imaginary; Nietzsche; Genealogy; Critique; Language